2020
DOI: 10.29292/jics.v5i2.323
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Film Lateral SOI PIN Diodes for Thermal Sensing Reaching the Cryogenic Regime

Abstract: This paper presents the performance of lateral SOI PIN diodes for temperature sensing in the range of 100 K to 400 K. Experimental results indicate that PIN diodes can be used to implement temperature sensors with high accuracy in cryogenic regime, provided that a suitable temperature range is chosen for calibration. Numerical simulations using Atlas two-dimensional simulator were performed in order to confirm this hypothesis and extend the analysis, verifying the accuracy of the existing model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It has been reported that the maximum current sensitivity to temperature changes can be observed in SCs where TE takes place [9][10][11][12][13][14][15][16][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Therefore, we should first look at whether the current flow through the present SBDs corresponds to TE.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that the maximum current sensitivity to temperature changes can be observed in SCs where TE takes place [9][10][11][12][13][14][15][16][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Therefore, we should first look at whether the current flow through the present SBDs corresponds to TE.…”
Section: Resultsmentioning
confidence: 99%
“…Perez et al [23] reported that the V-T curve for a bias current of 2.5 A cm −2 had a linear variation with an α value of 1.6 mV K −1 for diamond SBDs in the 300-440 K range. de Souza et al [24] presented an analysis of the performance of lateral PIN diodes for temperature sensing from 100 K up to 400 K [24] and reported that the α value of their all diodes increased with decreasing forward current, in agreement with the data reported in [25]. Chopra and Dharmadurai [25] found that the thermal sensitivity value increased from 2.07 mV K −1 at 1 mA to 2.76 mV K −1 at 10 µA from the linear V-T curves of the diodes in the temperature range 4 to 100 K.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations